Reforming Social Rights for International Refugees in Indonesia: Towards Enhanced Welfare and Legal Protection - Ayub Torry Satriyo Kusumo; Grishafa Anggita Erdiyasa; Etta Nethania; Anis Widyawati; Sri Lestari Rahayu (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
Refugees constitute a highly vulnerable population, frequently exposed to severe human rights violations or neglect. Refugees are often undergone variable restrictions like on speech, travel, education, and economic activities. Particularly at risk are their rights to decent work, livelihoods, and access to education for children. The inability to secure dignified work profoundly exacerbates the challenges in fulfilling educational rights within refugee communities. This article investigates the systemic vulnerabilities leading to the potential violation of these critical social rights for international refugees in Indonesia. This study was a social legal research applied as an interdisciplinary study, using normative doctrinal and enforcement implementation analysis. As a nation that has not ratified the 1951 Convention on the Status of Refugees, Indonesia operates without a comprehensive domestic legal framework explicitly governing refugee social rights. Nevertheless, its responsibilities as a member of the global community, coupled with inherent humanitarian principles, morally and ethically obligate the protection of these fundamental rights. Drawing on comparative legal analysis and good practices from other nations, this paper aims to identify specific areas for legal and policy reform in Indonesia. These reforms are crucial for providing adequate protection for refugees’ rights to work and education, within the practical capabilities of the state, and without compromising the security and public order rights of its citizens. Ultimately, this research underscores the urgent need for domestic legal reform to enhance refugee welfare and ensure their human dignity in Indonesia.